Paleoparasitological analysis of a coprolite assigned to a carnivoran mammal from the upper pleistocene touro passo formation, Rio Grande do Sul, Brazil - Cardia, Daniel F.F. [UNESP]; Bertini, Reinaldo J. [UNESP]; Camossi, Lucilene G. [UNESP]; Richini-Pereira, Virgínia B.; Losnak, Debora O.; Francischini, Heitor; Dentzien-Dias, Paula (FapUNIFESP (SciELO), 2021)
A paleoparasitological analysis was carried out on a large coprolite assigned to a carnivoran mammal, recovered from the Municipality of Uruguaiana, in the western region of the State of Rio Grande do Sul, Brazil, where the Upper Pleistocene Touro Passo Formation crops out. For this, an individual sample was extracted from the specimen using an electric drill, dissociated with 10% hydrochloric acid solution, washed with distilled water, and sifted through a 500 mesh Tyler sieve. After laboratory processing, the sediment retained on the sieve was mixed with glycerin and examined by optical microscopy, which revealed the presence of 14 protozoan oocysts and three nematode eggs. The morphological characteristics of the oocysts (i.e., spherical shape, thick-walled, internal zygote apparently at the beginning of sporulation, as well as their size) and of the eggs (i.e., ovoidal shape, rounded ends, smooth surface, thin-shelled, embryo in their interior, along with their morphometry) suggest that these specimens belong respectively to the orders Eucoccidiorida and Strongylida (Family Ancylostomatidae) represented by several parasitic species of the alimentary tract of modern carnivore. This is the first record of paleoparasites discovered in a vertebrate host from the Touro Passo Formation.
Keywords: Ancylostomatidae; Eucoccidiorida; Ichnology; Lujanian; Paleoparasitology